Numerical simulation of a crack emanating from a micro-cavity in the orthopedic cement by technical sub modeling of total hip prosthesis - Sahli Abderahmane; Ait Kaci Djafar; Zahi Rachid; Moulgada Abdelmadjid; Benbarek Smail (Fracture and Structural Integrity)
PMMA has important micro structural heterogeneities such as cavities, and its elastic behavior is greatly affected by the presence of defects that may imply its weakening and cause failure. In areas of high concentrations of stress and due to the presence of cavities, micro cracks appear after crushing cavities due to patient movements, and grow and weld to each other until they form a macro     fissure that propagates until the total removal of the prosthesis.. In this study, the existence of a crack emanating from  a cavity with a diameter of 0.7 mm was assumed; our assessment takes into account two parameters, the position of the crack in the cement and we calculated the stress intensity factor (SIF) in the proximal part of orthopedic cement.